The 'anti-Instagram': Using visual methods to study the college experiences of underrepresented students. Issue 4 (8th August 2022) - Arnold, Karen D.; Casellas Connors, Ishara
Abstract : Seventy-four students from underrepresented groups portrayed their first-semester college experience through privately-shared, captioned Instagram photos elicited by text message prompts. Longitudinal study analysis investigates the feasibility of this innovative visual data collection method, characterises the content of photos, and compares visual evidence to audio-diary data from the same students. The method succeeded in revealing detailed longitudinal accounts of students' transition into college. Descriptive captions allowed participants to interpret their own images without the need for interviews, centring power with the student rather than the researcher. As compared with photo elicitation, collecting captioned images offers a more manageable, cost-effective way of collecting longitudinal data from relatively large, geographically dispersed samples. High response rates suggest that a familiar social media format like Instagram is a good fit for young adults and a promising approach for recruiting and retaining low-income, first-generation, and racially underrepresented minority students in research studies.